Precarious employment and the risk of serious psychological distress: a population-based cohort study in Japan - Yuko Kachi; Toshiaki Otsuka; Tomoyuki Kawada (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: This study examines whether precarious employment increases the risk of serious psychological distress (SPD) in a nationally representative cohort of Japanese middle-aged people. METHODS: From 2005-2009, we followed 8486 male and 6736 female participants (aged 50-59 years) in the Longitudinal Survey of Middle-aged and Elderly Persons. All individuals were employed and free of SPD, cardiovascular disease, and cancer at baseline. The participants were classified into two groups based on their baseline employment contract: precarious and full-time permanent work. SPD was assessed at each year during the study, using the K6 scale, a self-rated 6-item scale that screens for mood or anxiety disorders. We used discrete-time survival analysis, with a complementary log-log link, to examine the effect of precarious employment on SPD incidence. RESULTS: During a maximum follow-up period of four years, 374 men and 364 women developed SPD. Male precarious employees were more likely to develop SPD than male full-time permanent employees (hazard ratio 1.79, 95% confidence interval 1.28-2.51) in the full model, after adjusting for sociodemographic and occupational factors, cardiovascular disease risk, and K6 scores at baseline. By contrast, no significant association was observed among female employees. However, an analysis stratified by marital status revealed an association similar to that found among men but only among unmarried women. CONCLUSIONS: The findings suggest that precarious employment is associated with double the risk of SPD incidence among middle-aged Japanese men and - when stratified by marital status - among unmarried women. This highlights a major gender difference in the association between precarious employment and risk of SPD.